Oil Palm Empty Fruit Bunch-Derived Cellulose Acetate-Zeolite Mixed Matrix Membrane Adsorbers (MMMAs) for Ammonia Removal in Palm Oil Mill Effluent Wastewater Treatment - Cut Riski; Julinawati Julinawati; Mutia Farida; Mohd Rashidi Abdull Manap; Saiful (CV FOUNDAE, 2026)
This study developed cellulose acetate-zeolite mixed matrix membrane adsorbers (CA-zeolite MMMAs) using cellulose acetate synthesized from OPEFB as the polymer matrix and natural mordenite zeolite as the adsorptive inorganic filler. The membranes were fabricated to enhance ammonia-nitrogen removal from synthetic ammonia solution and palm oil mill effluent (POME). Zeolite incorporation improved several membrane properties, including pure water flux, swelling degree, and porosity, compared with pristine cellulose acetate membranes. However, tensile strength and elongation decreased after zeolite addition, indicating a trade-off between adsorption-related properties and mechanical flexibility. The optimum adsorption performance was achieved using the CA-zeolite MMMA with 30% zeolite loading and a contact time of 70 min, producing an ammonia adsorption capacity of 1.051 mg/g under the selected operating conditions. Adsorption kinetic analysis showed that the pseudo-second-order model provided a better fit than the pseudo-first-order model, with an R² value of 0.9104. The adsorption equilibrium was better represented by the Langmuir isotherm model, with an R² value of 0.9247. The optimized membrane also showed regeneration potential, with first-cycle regeneration efficiencies of 83.37% using NaCl and 73.52% using HCl. When applied to actual POME, the membrane reduced ammonia concentration from 173.93 mg/L to 50.161 mg/L in batch adsorption and 52.136 mg/L in filtration, corresponding to removal efficiencies of 71.16% and 70.02%, respectively. Although the treated effluent remained above the regulatory discharge limit of 20 mg/L, the results demonstrate that OPEFB-derived CA-zeolite MMMAs have potential as pretreatment or polishing materials for ammonia-nitrogen removal from POME.